Commorientes. Einige Bemerkungen zu dem Rechtsinstitut im polnischen Zivilrechtsystem - Aldona Rita Jurewicz (Clio@Themis, 2021)
This paper is devoted to the issue of the presumption of death of two or more people at the same time according to the Polish civil law (art. 32 KC). The author presents the problems of legal interpretation (linguistic and systematic) and of the necessary premises for applying this type of presumption according to the Polish civil law doctrine. It also brings up the issue of doubts about questioning the simultaneous death presumption.